FIELD EXPERIENCE CHALLENGES: EXPLORING THE DIFFICULTIES OF PPG ENGLISH EDUCATION STUDENTS AT FKIP UIR, PEKANBARU - Rugaiyah, Rugaiyah; Putri, Miranti Eka; Khulaifiyah, Khulaifiyah; Idayani, Andi; Mulyani, Ari (English Review: Journal of English Education, 2024)
This research aims to determine the difficulties of English Language Education PPG students at FKIP UIR in carrying out the field experience program in Pekanbaru, Riau. This research is a type of descriptive research that uses a qualitative approach. The subjects of this research were 10 students of PPG English education at FKIP UIR who were carrying out a field experience program in Pekanbaru in the 2023/2024 academic year. Data collection in this research used a questionnaire technique and the data analysis technique used a percentage test. Based on the results of data analysis, it was found that the difficulties of PPG English Language Education FKIP UIR students in carrying out lesson opening activities were classified as low, the difficulties in mastering the learning material were classified as low, the difficulties in applying educational learning strategies were classified as moderate, the difficulties in applying the scientific approach were classified as moderate, the difficulties The use of learning resources and media is relatively low, the difficulty in involving students in learning is very low, and the difficulty in carrying out lesson closing activities is very low. Overall, the level of difficulty for English Language Education PPG students at FKIP UIR in carrying out PPL is relatively low with a difficulty which shows that PPG English language education students at FKIP UIR Pekanbaru Riau do not experience difficulties in implementing it.